2020
DOI: 10.3390/ijms21218225
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Pre-Instructed HSCs Robustly Execute Asymmetric Cell Divisions In Vitro

Abstract: Hematopoietic stem cells (HSCs) are responsible for life-long production of all mature blood cells. Under homeostasis, HSCs in their native bone marrow niches are believed to undergo asymmetric cell divisions (ACDs), with one daughter cell maintaining HSC identity and the other committing to differentiate into various mature blood cell types. Due to the lack of key niche signals, in vitro HSCs differentiate rapidly, making it challenging to capture and study ACD. To overcome this bottleneck, in this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Because molecular differences between daughter cells can be explained by stochastic processes, cell-cell interaction, signals from the microenvironment, or ACD, an important next step will be to integrate single-cell genomics and live-cell imaging to obtain further mechanistic insights. [63], CD133 [64], CDC42 [57] [67 ]: The low number of purified HSCs, their high motility and low adhesion pose major technical challenges to capture HSCs during divisions. Most candidates were therefore not analyzed in HSCs but other cell types.…”
Section: Evidence For Asymmetric Paired Hematopoietic Stem Cell Daugh...mentioning
confidence: 99%
See 2 more Smart Citations
“…Because molecular differences between daughter cells can be explained by stochastic processes, cell-cell interaction, signals from the microenvironment, or ACD, an important next step will be to integrate single-cell genomics and live-cell imaging to obtain further mechanistic insights. [63], CD133 [64], CDC42 [57] [67 ]: The low number of purified HSCs, their high motility and low adhesion pose major technical challenges to capture HSCs during divisions. Most candidates were therefore not analyzed in HSCs but other cell types.…”
Section: Evidence For Asymmetric Paired Hematopoietic Stem Cell Daugh...mentioning
confidence: 99%
“…To date, NUMB [28 ▪ ,33,59], CD53 [60], CD62L [60], CD63 [28 ▪ ,60], CD71 [60], AP2A2 [28 ▪ ,61], TIE-2 [62], Myosin-II [63], CD133 [64], CDC42 [57], LAMP-1 [28 ▪ ], LAMP-2 [28 ▪ ], LC3β [28 ▪ ], TMRM [65 ▪▪ ], COX8a [66 ▪▪ ], GLUT1 [67 ▪ ], JAM3 [67 ▪ ] and HK2 [67 ▪ ] were postulated to be asymmetrically inherited during HSPC divisions. However, due to technical shortcomings used for their identification, most require additional experimental confirmation [51 ▪ ]: The low number of purified HSCs, their high motility and low adhesion pose major technical challenges to capture HSCs during divisions.…”
Section: Asymmetric Inheritance During Hematopoietic Stem Cell Divisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recent data have shown that JAM-C was asymmetrically distributed upon HSC division after in vivo IFNα activation, the paired daughter cells expressing JAM-C being the most immature one. 20 This demonstrates that JAM-C is a robust marker/tool to decipher mechanisms controlling HSC maintenance and activation within the BM microenvironment.…”
mentioning
confidence: 94%
“…After BM transplantation, only the successful homing of HSCs can ensure that the long-term repopulation of the blood system is initiated. Thus, improving low efficacy in the engraftment of clinical hematopoietic transplantation has become an important challenge in the treatment of previously incurable hematopoietic diseases over the past few decades [ 4 ]. For years, available sources of HSCs are the BM, circulating peripheral blood and umbilical cord blood (UCB).…”
Section: Introductionmentioning
confidence: 99%